Effectiveness of Software Project Management Based on Capability Maturity Model Integration in the Implementation of Secure Software Development Life Cycle at PT XYZ - Muhammad Hanifudin; Hussein Satrio (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study evaluates the implementation of the Secure Software Development Life Cycle (S-SDLC) and examines the effectiveness of software project management based on the Capability Maturity Model Integration (CMMI) version 3 at PT Magicsoft Teknologi Indonesia. A qualitative research approach was employed using in-depth interviews, observations, and documentation analysis. Empirical findings were triangulated and mapped against S-SDLC indicators and twelve CMMI v3 Practice Areas (PAs) grouped into Doing, Managing, and Enabling. The findings indicate that S-SDLC has been integrated throughout the software development lifecycle, positioning security as a built-in process rather than a reactive add-on. Security-relevant practices collectively enhance software quality, system stability, and preventive security governance. With regard to project management effectiveness, the study shows that most PAs reached Capability Level 3 (Defined), reflecting a mature level of process standardization at the project level. However, effectiveness was more prominent in terms of quality, security, and process control, while schedule performance faced pressure due to workload imbalances and resource capacity constraints. These findings highlight that software project effectiveness is inherently multidimensional and cannot be assessed solely through schedule adherence. The study contributes to theory by demonstrating that CMMI v3 can serve as an evaluative framework compatible with S-SDLC and enriches project management discourse by positioning security as an integral dimension of process effectiveness. Practically, the study provides a fit-for-purpose internal evaluation framework for software development organizations seeking to improve process maturity without formal appraisal.